Disentangling the factors that shape bromeliad and ant communities in the canopies of cocoa agroforestry and preserved Atlantic Forest. (6th October 2021) - DaRocha, Wesley; Antoniazzi, Reuber; Delabie, Jacques H. C.; Schroth, Götz; Fernandes, Geraldo W.; Neves, Frederico S.
Abstract: In tropical forest canopies, host tree characteristics shape epiphyte communities, and both host tree characteristics and epiphytes determine invertebrate communities, for example, ants. Tree height is among the factors most often mentioned as a strong predictor for both bromeliad and ant communities. However, many factors interact dynamically in shaping the tree–bromeliad–ant association. Here, we investigated the effects of the host tree and canopy structural characteristics on both bromeliads and ants. We sampled bromeliads on 180 trees and ants in 360 bromeliads living on a subset of 60 of those trees in a continuum of native forest fragments and agroforestry systems in the Atlantic Forest, a Brazilian biodiversity hotspot. We found that the host trees' crown area had a positive effect on the abundance of bromeliads. Also, the introduced tree species had higher abundance of bromeliads than native tree species. Moreover, we found that the ant species composition was different between native and introduced trees. In addition, we observed a positive effect of the size of bromeliads and tree crown height on ant species richness on both bromeliad and tree scales, but there was no effect of tree height. Taken together, our findings highlight the importance of trees with large crowns for the maintenance of bromeliads, which are also associated with richer ant communities in both Atlantic Forest and agroforestry systems. These results emphasize the importance of trees with larger crowns for biodiversity conservation in both native forest fragments and agroforestry systems. Abstract in Portuguese is available with online material. Abstract : Higher tree crown area and trees of introduced species have a higher abundance of bromeliads; bromeliads with a high size higher tree crown heights increase the ant species richness on both bromeliad and tree scales. Resumo: No dossel de florestas tropicais as características das árvores determinam as comunidades de epífitas e dos invertebrados associados, como por exemplo as formigas. A altura das árvores está entre os fatores mais frequentemente mencionados como uma característica que determina tanto as comunidades de bromélias quanto as de formigas. Entretanto, outras características interagem na associação de bromélias e formigas. Aqui, investigamos os efeitos das características estruturais da árvore hospedeira e do dossel, tanto para bromélias como para formigas. Registramos a abundância de bromélias em 180 árvores e amostramos formigas em um subconjunto de 60 dessas árvores em um continuum de fragmentos de floresta nativa e sistemas agroflorestais na Mata Atlântica, um hotspot brasileiro de biodiversidade. Encontramos que a área das copas das árvores hospedeiras tem um efeito positivo sobre a abundância de bromélias. Além disso, as espécies de árvores introduzidas apresentaram uma maior abundância de bromélias se comparadas às árvores nativas. Além disso, encontramos que a composição de espécies de formigas difere entre árvores nativas e introduzidas. Adicionalmente, observamos um efeito positivo do tamanho das bromélias e da altura das copas das árvores sobre a riqueza de espécies de formigas, tanto na escala bromélia como na escada árvore, mas não foi verificado um efeito da altura total das árvores. Nossas descobertas destacam a importância de árvores com copas grandes para a manutenção das bromélias, que também estão associadas à maior riqueza das comunidades de formigas tanto na Mata Atlântica nativa quanto em sistemas agroflorestais. Estes resultados enfatizam a importância da manutenção de árvores com copas grandes para a conservação da biodiversidade, tanto em fragmentos de floresta nativa quanto em sistemas agroflorestais.